Mediation and Totality: Jameson and the Linguistic Turn - García Quesada, George (2025)
Although Fredric Jameson's work usually refers us to cultural objects of a literary or artistic nature, the scope of his theorization has reached other important contemporary discussions. Such is the case of the linguistic turn predominant in the field of the Philosophy of history in the last 50 years. His theory of narrative as a socially symbolic act, which adopts structuralist approaches in a dialectical matrix, distanced him from the rising narrativist positions, as well as from positions that do not sufficiently problematize narrative in historical knowledge. This article, in homage to the fundamental North American Marxist theorist, examines this problem in his conception of historiographical narrative, primarily considering his approaches in The Political Unconscious (1981) and The Valences of History (2009).